Fluoride concentration and stability in commonly used dentifrices in Sri Lanka - Niroshani Surangika Soysa; Jaime Aparecido Cury; Chrisman Neil Roshan Alexander Alles (Universidade Estadual de Campinas, 2018)
According to the best scientific evidence, a dentifrice should contain 1000 ppm F or above but to guarantee the anti-caries efficacy this concentration should be chemically soluble and remain stable until the dentifrice expiration date. This stability depends on the type of abrasive and fluoride salt used in the formulation. Nine brands of dentifrices purchased in the Sri Lankan market were evaluated. The total fluoride (TF = soluble + insoluble) and total soluble fluoride (TSF = ion MFP + ion F-) concentrations were determined in fresh samples and after storage at room temperature and after accelerated aging. The analyses were made with an ion specific electrode using a validated analytical method. Three dentifrices were formulated with MFP/CaCO3, two with MFP/Silica, two with NaF/Silica and two were not fluoridated. The TF concentration found was very close to the concentration declared by the manufacturer. However, even in the fresh sample of one dentifrice formulated with MFP/CaCO3, there was insoluble fluoride (22%). The TSF concentration in all MFP/CaCO3-based dentifrices decreased with storage while insoluble fluoride had increased. The dentifrices formulated with MFP/Silica and NaF/Silica showed chemical stability. This is the first study done about the chemical quality of fluoride dentifrices marketed in Sri Lanka and the findings are an alert for a surveillance system in the country.